PEMODELAN PEMBIMBINGAN PRAKTIK PEMANTAPAN KEMAMPUAN PROFESIONAL (PKP) PADA MAHASISWA PENDIDIKAN JARAK JAUH MELALUI LESSON STUDY - Suhartono, Suhartono; Suhartono, Suhartono; Darmayanti, Tri (LPPM Universitas Terbuka, 2015)
This study aims to generate an effective way of guiding the practice of Professional Capabilities Stabilization (Pemantapan Kemampuan Profesional/PKP) and is used to enhance the ability of S1 PGSD-UT student in the learning improvement. Through lesson study in PKP considered important, because theoretically, provide a way for teachers to improve learning systematically (Podhorsky, C., & Fisher, D., 2007). As the program estuary of S1 PGSD-UT program, this program is the culmination of a course that has been followed earlier by S1 students PGSD. Through PKP, students are expected to have better professional skills in applying the principles of action research (PTK) to find, analyze, and formulate learning problems encountered. The study was conducted with a participatory or emancipatory paradigm approach as set out basic concepts of participatory action reseach (McTaggart, R., 1991, Carr and Kemmis, 1990, Connole, 1993). The study was conducted in 2014 with 34 students S1 PGSD-UT as a sample. The research method using observation, learning journals, interviews, and documentaries. Results showed that the lesson study as a model for professional development of educators through collaborative learning and continuous assessment based on the principles of collegiality and mutual learning to build a learning community. Lesson study selected and implemented the guidance PKP be an effective way to improve the quality of learning and teaching in the classroom. The development of lesson study conducted and based on the